Co-creation melalui media sosial: Kajian Pada Kampanye "Share a Coke" Kasus Coca Cola di Indonesia - Saifuddin Zuhri; Toto Heru Dwihandoko; Rahayu Rahayu (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2025)
Abstract Co-creation has become a compelling concept in innovation involving companies and customers. Communication between companies and consumers is now seen as a central factor in the success of both existing and new products or services. Numerous studies have emphasized the importance of co-creation through active customer participation. In today's era of consumer sovereignty, social media platforms and corporate websites have become major enablers of user-generated content. This study explores customer co-creation through social media, using Coca-Cola's “Share a Coke” campaign as a case study. This campaign, recognized as one of the most iconic co-creation initiatives, was launched in several countries, including Indonesia. The research applies a qualitative method to examine how social media platforms facilitated the interaction between brand and consumer, allowing customers to become co-creators of value. In Indonesia, the campaign replaced the Coca-Cola logo on bottles with 70 popular local names, encouraging consumers to share their personalized experiences online. The study finds that co-creation in this campaign was driven not only by promotional incentives but also by emotional, social, and psychological motivations. It also highlights how digital marketing and social media have shifted power from companies to consumers, positioning the consumer as an active participant in branding and innovation.